THEORETICAL AND METHODOLOGICAL BASES OF FORMATION OF LISTENING COMPREHENSION SKILLS IN STUDENTS - No’monov Istiqbol Iqboljonovich (Galaxy International Interdisciplinary Research Journal, 2021)
This article analyzes a number of listening comprehension problems and solutions for musicians and students studying in this field. It is widely covered as an example of contemporary and 20th century music.